(untitled) (Costos y Gestión, 2022)
In recent times, the economic environment in which companies operate is characterized by a greater need for continuous improvement and the necessary flexibility to adapt to changes. Therefore, it is required that they act as a system in which all its components have a common objective, work in an integrated manner and are truly interrelated. The research is based on a conceptual theoretical framework based on strategic direction, in order to achieve the goals and objectives proposed in the organization, to achieve boom and growth; in which the internal and external analysis of the entity influences to identify opportunities, threats, strengths and weaknesses. Hence, the objective pursued is: to carry out the analysis of the strategic management in the Poultry company of Pinar del Río, in order to design an adequate strategy so as not to spend unnecessary economic-financial resources and be in a position to make decisions to respond to the demands of the competitive environment.